Elicitation: A Tool for Enriching the Bioactive Composition of Foods - Nieves Baenas; Cristina García-Viguera; Diego A. Moreno (Molecules, 2014)
Elicitation is a good strategy to induce physiological changes and stimulate defense or stress-induced responses in plants. The elicitor treatments trigger the synthesis of phytochemical compounds in fruits, vegetables and herbs. These metabolites have been widely investigated as bioactive compounds responsible of plant cell adaptation to the environment, specific organoleptic properties of foods, and protective effects in human cells against oxidative processes in the development of neurodegenerative and cardiovascular diseases and certain types of cancer. Biotic (biological origin), abiotic (chemical or physical origin) elicitors and phytohormones have been applied alone or in combinations, in hydroponic solutions or sprays, and in different selected time points of the plant growth or during post-harvest. Understanding how plant tissues and their specific secondary metabolic pathways respond to specific treatments with elicitors would be the basis for designing protocols to enhance the production of secondary metabolites, in order to produce quality and healthy fresh foods.